Phase-selective Floquet engineering in a charge density wave material - Fei Wang; Xuanxi Cai; Teng Xiao; Changhua Bao; Haoyuan Zhong; Wanying Chen; Tianyun Lin; Tianshuang Sheng; Xiao Tang; Hongyun Zhang; Pu Yu; Zhiyuan Sun; et al. (Proceedings of the National Academy of Sciences, 2026)
Floquet engineering has emerged as a powerful approach for dynamically tailoring the electronic structures of quantum materials through time-periodic light fields. The light fields generated by ultrafast laser pulses can transiently dress Bloch electrons, creating novel electronic states inaccessible in equilibrium. While such temporal modulation provides a dynamic control, spatially periodic modulations, such as those arising from charge density wave (CDW) order, can also dramatically reconstruct the electronic structure through real-space symmetry breaking. The interplay between these two distinct forms of modulation—temporal and spatial—opens a frontier in phase-selective Floquet engineering. Here we demonstrate this concept experimentally in the prototypical CDW material 1T-TiSe 2 . Using time- and angle-resolved photoemission spectroscopy with mid-infrared pumping, we observe a striking momentum-dependent pump-induced instantaneous downshift of the valence band maximum (VBM), which is in sharp contrast to the subsequent upward shift on picosecond timescale associated with CDW melting. Remarkably, the light-induced VBM downshift is observed exclusively in the CDW phase and only when the pump pulse is present, reaching maximum when pumping near resonance with the CDW gap. These observations unequivocally reveal the critical role of CDW in enabling the phase-selective Floquet engineering of TiSe 2 . Our work demonstrates how time-periodic drives can synergistically couple to spatially periodic modulations, establishing a paradigm for phase-selective Floquet engineering enabled by spontaneous symmetry breaking.